Activity of Manau Rattan (Calamus manan) Seeds Extract on Reducing Blood Glucose Levels of Male Swiss Webster Mice - Risyda Komaliya; Saftia Aryzki; Clara Montella; Devi Norlita; Jaki Mubarak (Berkala Kedokteran, 2025)
Diabetes mellitus is a degenerative disease characterized by high blood sugar levels caused by disturbances in insulin secretion in the body. One alternative in dealing with diabetes mellitus is traditional medicine using natural ingredients. One of the plants that has the potential to have anti-diabetic activity is the Manau Rattan Seed (Calamus manan). This study aims to determine the decrease in blood glucose levels of Swiss Webster male white mice using the experimental method with the glucose tolerance method. The test animals were divided into seven groups, namely group I being a negative control given glucose 2 g/Kg BW, groups II and III being positive controls each given metformin at a dose of 1.3 mg/Kg BW, and glibenclamide at a dose of 0 .65 mg/Kg BW, and groups IV, V, VI and VII became the test material from manau rattan seed extract with respective levels of 100 mg/Kg BW, 200 mg/Kg BW, 300 mg/Kg BW, and 400 mg/Kg BW. Based on the results of the data, the percentage of decreased blood glucose levels (%) showed that the best reduction in glucose levels was in group III (glibenclamide) with an average yield of 41.95%. Parametric analysis used One Way ANOVA with a significance value of >0.05, namely 0.431, so there was no significant difference.